2020
DOI: 10.5116/ijme.5eb6.70c6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac auscultation skills among junior doctors: effects of sound simulation lesson

Abstract: Objectives: To evaluate the effect of a sound simulation lesson to improve cardiac auscultation skills among junior doctors. Methods: This study is based on the design of test comparison before and after educational intervention using a convenient sample. For 50 junior doctors in Japan, diagnostic accuracy before and after a sound simulation lesson for cardiac auscultation skills was compared. There were 15 doctors who experienced cardiology rotation. The lesson used seven abnormal cardiac recordings (third he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Simulators successfully provided good correlation between the users’ results and their previous experience and knowledge [ 46 ]. Additionally, simulators’ benefits for the acquisition of knowledge and skills have been well characterized [ 34 ], ranging from auscultation skills among junior doctors [ 47 ] to highly technical ones in demanding surgical specialties [ 2 ]. This is why there has been a long tradition of their use in the history of Medical Education [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simulators successfully provided good correlation between the users’ results and their previous experience and knowledge [ 46 ]. Additionally, simulators’ benefits for the acquisition of knowledge and skills have been well characterized [ 34 ], ranging from auscultation skills among junior doctors [ 47 ] to highly technical ones in demanding surgical specialties [ 2 ]. This is why there has been a long tradition of their use in the history of Medical Education [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although case simulations and virtual standardized patients can provide some training of skills such as physical examination and clinical reasoning, these activities are generally supplementary rather than a replacement of in-person teaching. [35][36][37][38][39][40] Moreover, competency-based assessments of student skills through these virtual simulations are limited. Anecdotally, virtual objective structured clinical examinations can be used to evaluate remaining competencies required for graduation, but these techniques have never before served as substitutes for direct patient care.…”
Section: Challengesmentioning
confidence: 99%
“…1 Despite its critical importance, studies have shown that the proficiency of medical professionals in performing cardiac auscultation is in a steady decline. [2][3][4] This decline is particularly evident in a study by Mangione and colleagues that showed only 20% of the graduating medical class could accurately diagnosis cardiac sounds. They concluded that this result may be largely due to curriculum deficiencies in teaching cardiac auscultation.…”
Section: Introductionmentioning
confidence: 99%